Traceless bioresponsive shielding of adenovirus hexon with HPMA copolymers maintains transduction capacity in vitro and in vivo - Prill, Jan-Michael; Subr, Vladimír; Pasquarelli, Noemi; Engler, Tatjana; Hoffmeister, Andrea; Kochanek, Stefan; Ulbrich, Karel; Kreppel, Florian (PloS one, 2014)
Capsid surface shielding of adenovirus vectors with synthetic polymers is an emerging technology to reduce unwanted interactions of the vector particles with cellular and non-cellular host components. While it has been shown that attachment of shielding polymers allows prevention of undesired interactions, it has become evident that a shield which is covalently attached to the vector surface can negatively affect gene transfer efficiency. Reasons are not only a limited receptor-binding ability of the shielded vectors but also a disturbance of intracellular trafficking processes, the latter depending on the interaction of the vector surface with the cellular transport machinery. A solution might be the development of bioresponsive shields that are stably maintained outside the host cell but released upon cell entry to allow for efficient gene delivery to the nucleus. Here we provide a systematic comparison of irreversible versus bioresponsive shields based on synthetic N-(2-hydroxypropyl)methacrylamide (HPMA) copolymers. In addition, the chemical strategy used for generation of the shield allowed for a traceless bioresponsive shielding, i.e., polymers could be released from the vector particles without leaving residual linker residues. Our data demonstrated that only a bioresponsive shield maintained the high gene transfer efficiency of adenovirus vectors both in vitro and in vivo. As an example for bioresponsive HPMA copolymer release, we analyzed the in vivo gene transfer in the liver. We demonstrated that both the copolymer's charge and the mode of shielding (irreversible versus traceless bioresponsive) profoundly affected liver gene transfer and that traceless bioresponsive shielding with positively charged HPMA copolymers mediated FX independent transduction of hepatocytes. In addition, we demonstrated that shielding with HPMA copolymers can mediate a prolonged blood circulation of vector particles in mice. Our results have significant implications for the future design of polymer-shielded Ad and provide a deeper insight into the interaction of shielded adenovirus vector particles with the host after systemic delivery.
Keywords: technika přenosu genů; signální transdukce; Signal Transduction; methakryláty; neparametrická statistika; Fluorometry; genetické vektory; Microscopy, Confocal; Female; Blotting, Western; konfokální mikroskopie; Capsid Proteins; myši inbrední BALB C; zvířata; myši; Immunohistochemistry; molekulární struktura; imunohistochemie; Mice; Mice, Inbred BALB C; Molecular Structure; ženské pohlaví; fluorometrie; organické látky; Organic Chemicals; polymerázová řetězová reakce; Polymerase Chain Reaction; virové plášťové proteiny; Statistics, Nonparametric; Genetic Vectors; Animals; western blotting; Methacrylates; Gene Transfer Techniques